Effectiveness of applying Intradialytic Stretching Exercises on Reducing Lower Limbs Muscle Cramps among Haemodialysis Patients (Medical Forum Monthly, 2026)
Objective: To evaluate the effectiveness of intradialytic stretching exercises in reducing lower-limb muscle cramps among patients undergoing maintenance hemodialysis.Study Design: Quasi-experimental pre-test–post-test control group study.Place and Duration of Study: This study was conducted at selected hemodialysis centers in Mosul, Iraq, from 25th February 2026 to 25th April 2026.Methods: A purposive sample of 60 adult patients receiving maintenance hemodialysis was recruited and allocated into a study group (n = 30) and a control group (n = 30). The study group performed a structured intradialytic stretching exercise program during the second hour of each dialysis session in addition to routine nursing care, whereas the control group received routine care only. Muscle cramp severity was assessed using the Muscle Cramp Questionnaire, and pain intensity was measured using the Visual Analogue Scale (VAS). Data were analyzed using descriptive and inferential statistics, including the Friedman, Wilcoxon signed-rank, and Mann–Whitney U tests, with statistical significance set at p < 0.05.Results: Patients who participated in the stretching exercise program demonstrated significant reductions in muscle cramp severity and pain intensity compared with the control group (p < 0.001). At the final assessment, 83.3% of participants in the intervention group reported no muscle cramps, while only minimal improvement was observed inthe control group. The intervention also improved patient comfort and tolerance of hemodialysis sessions.Conclusion: Intradialytic stretching exercises are a safe, simple, and effective nurse-led intervention for reducing lower-limb muscle cramps among maintenance hemodialysis patients. Incorporating this intervention into routine hemodialysis care may improve symptom management and enhance patients' quality of life.